2020
DOI: 10.3389/fpsyg.2020.01646
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Emotion Regulation, Alexithymia, and Social Phobia Are Associated With Disordered Eating in Male and Female Undergraduate Athletes

Abstract: Investigations of disordered eating in the athlete population tend to focus on females and the influence of sport level. This leaves unanswered whether, and how, team interdependence (i.e., whether the competition is engaged with one person or as a team) may differentially impact male athletes. In the present study, we recruited a sample of non-athletes, individual athletes, and team athletes and examined the interaction of gender and teammate interdependence on established psychosocial risk factors for disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 112 publications
1
13
0
Order By: Relevance
“…Further limitations are that there was a lack of uniformity in the measuring instruments, especially for PA assessment. For the RCTs, assessment tools varied from standardized questionnaires (Herring et al, 2014;Ashdown-Franks et al, 2017;Ren and Li, 2020) and self-constructed questionnaires to single items (Atalay and Gençöz, 2008;Dimech and Seiler, 2010;Rocha et al, 2014;Üstün and Yapici, 2019;Benau et al, 2020), or PA was divided into different categories, time, and modes of exercise (Goodwin, 2003;Dong et al, 2018;Koç and Dündar, 2018;Kim et al, 2020). For the longitudinal and cross-sectional studies, the instruments that were used for PA assessment also ranged from one-item assessments to standardized questionnaires.…”
Section: Overall Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further limitations are that there was a lack of uniformity in the measuring instruments, especially for PA assessment. For the RCTs, assessment tools varied from standardized questionnaires (Herring et al, 2014;Ashdown-Franks et al, 2017;Ren and Li, 2020) and self-constructed questionnaires to single items (Atalay and Gençöz, 2008;Dimech and Seiler, 2010;Rocha et al, 2014;Üstün and Yapici, 2019;Benau et al, 2020), or PA was divided into different categories, time, and modes of exercise (Goodwin, 2003;Dong et al, 2018;Koç and Dündar, 2018;Kim et al, 2020). For the longitudinal and cross-sectional studies, the instruments that were used for PA assessment also ranged from one-item assessments to standardized questionnaires.…”
Section: Overall Discussionmentioning
confidence: 99%
“…In five studies (Atalay and Gençöz, 2008;Dimech and Seiler, 2010;Rocha et al, 2014;Üstün and Yapici, 2019;Benau et al, 2020), PA was assessed through self-constructed questionnaires or questions, such as "How often do you get physical exerciseeither on your job or in recreational activity?" In four studies (Goodwin, 2003;Dong et al, 2018;Koç and Dündar, 2018; Kim (Dishman and Steinhardt, 1988); CIDI, the Composite International Diagnostic Interview (WHO, 1990); CL, clinical (Connor et al, 2000); IPAQ, The International Physical Activity Questionnaire (Craig et al, 2003); K-MPAI, Kenny MPA Inventory Questionnaire (Rocha et al, 2011); LSAS-SR, Liebowitz Social Anxiety Scale-Self-Report (Liebowitz et al, 1985;Fresco et al, 2001); MINI-KID, Mini International Neuropsychiatric Interview for Children and Adolescents (Sheehan et al, 2010); N, sample size; NA, not applicable; NCL, non-clinical; NR, not reported; PA, physical activity; PARS-3, Physical Activity Rating Scale (Liang, 1994); PDSQ, the Psychiatric Diagnostic Screening Questionnaire (Zimmerman et al, 1999); SA, social anxiety; SAS, The Social Anxiety Scale (Özbay and Palanci, 2001); SASC, Social Anxiety Scale for Children (La Greca et al, 1988), originally adapted from the Social Anxiety Scale for Children-Revised (La Greca and Stone, 1993); SD, standard deviation; SPAIK, The German Version (SPAIK) of the Social Phobia and Anxiety Inventory for Children (SPAI-C;…”
Section: Assessment Of Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, parental stress for high marks in English is the leading cause of examination phobia influencing students' emotional aspects (e.g., Bussone et al, 2020), which were discussed as phobic, psychological, emotional, and cognitive components (e.g., Benau et al, 2020;Gustems-Carnicer& Calderón, 2013). These components are based on extreme pressure, thinking of failure, worrying about possible outcomes and mental stress, and negative thoughts (Sarason&Sarason, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the low levels of phobia are considered as compromised responses. However, when phobia exceeds its normal level, it damages various parts of life, such as social relationships [8]. Social phobia is the severe and constant fear of situations in which the person is faced with others or has to do something in front of them [9].…”
Section: Introductionmentioning
confidence: 99%